To Compare the Outcomes of Bipolar Electro Cautery Tonsillectomy Vs Cold Steel Dissection Pediatric Tonsillectomy in Terms of Mean-Operative Time and Intra-Operative Blood Loss - Waqas Javaid, Muhammad Naeem, Syed Tauseef Bukhari, Syed Muhammad Azeem, Bilal Zahid, Sultan Badar Munir, Maryam Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the most popular surgical operations performed using a variety of techniques is a tonsillectomy. The two that are used the most frequently are the traditional cold dissection technique (CDT) and electrocautery, the latter of which is carried out using the monopolar and bipolar electrocautery procedures (BET).All techniques used during tonsillectomy are intended to lessen perioperative bleeding, the intensity of felt pain, and postoperative morbidities. Aim: To compare the outcomes of the bipolar electro cautery tonsillectomy versus cold steel dissection pediatric tonsillectomy in terms of mean-operative time and intra-operative blood loss. Setting: ENT department of Sir Ganga Ram Hospital, F.J. Medical University Lahore from 11-03-2022 to 10-09-2022 Study design: Randomized Controlled Trial Study type: Quantitative study type Methods: The sample size of 110 (55 in group A 55 in group B) was estimated by using 95% confidence level, 90% power of test with an anticipated mean loss of blood during surgery of tonsillectomy i.e. 7.38±2.81m1 with bipolar electro cautery dissection and 11.73±2.86 ml with cold steel dissection. Results: One hundred and ten patients were included as per calculated sample size with the mean age of 8.96±2.42 years. The lowest age limit of children was 5 years while the maximum age limit of children was 13 years. In group A, the mean age of children was 8.80±2.46 years. In group B, the mean age of children was 9.13±2.38 years. The difference was observed as insignificant i.e. p–value = 0.481. Of 110 patients, 67(60.91%) patients were male whereas in group B 29(52.7%) were males. Similarly in group A 17(30.9%) were females and 26(47.3%) were females. The difference was observed as insignificant i.e. p–value = 0.079.In group A, the mean operative time was 19.76±4.47 minutes. Conclusion: This study concluded that bipolar electro cautery tonsillectomy showed significantly better outcome as compared to cold steel dissection pediatric tonsillectomy. Keywords: Cold dissection tonsillectomy, Electrocautery tonsillectomy, Mean operative time, Intra operative blood loss.